Resilient cooling pathway for extremely hot climates in southern Asia. (1st November 2022) - Mehmood, Sajid; Lizana, Jesus; Núñez-Peiró, Miguel; Maximov, Serguey A.; Friedrich, Daniel
Highlights: Parametric analysis of resilient cooling solutions in an extremely hot region. Evaluation of synergies & trade-offs with regard to energy savings and comfort hours. Night ventilation and solar protection provide the highest synergies. Insulation and airtightness without improved ventilation provide important trade-offs. Ventilation and higher thermostat settings are key points toward resilience. Abstract: Global warming is increasing extreme heat conditions, with existing energy efficiency policies showing trade-offs between mitigation objectives and adaptation to climate change. This research aims to identify the best resilient cooling solutions that should be promoted in the built environment of extremely hot countries to increase their heat resilience capacity. The impact of climate change on climate zones, cooling thermal demand (kWh/m 2 ), and indoor heat discomfort hours (DHh, hours) in buildings is evaluated in different extremely hot dry climates of southern Asia through a parametric analysis for 2020, 2050 and 2080 under the A2 (medium–high) emission scenario. Then, cooling alternatives with higher synergies and trade-offs between energy efficiency (energy consumption) and resiliency to extreme heat (passive survivability) are highlighted. TRNSYS simulation software and ASHRAE criteria were used to characterise climate zones and calculate buildings' cooling needs and discomfort hours. Pakistan, in southern Asia, was selected as a hot reference region characterised by various climatic regions. The simulated scenario shows how Pakistan's extremely hot dry climate surface may increase from 36.9 % to 78.1 % by 2080, increasing annual cooling needs ranging from 20.56 to 66.96 kWh/m 2 and indoor discomfort hours ranging from 423 to 1267 h. The results demonstrate how the passive solutions with higher synergies between energy savings and indoor comfort hours are, in decreasing order, ventilative cooling, reflective and ventilated roofs, shading in windows, and roof insulation. They can provide energy savings ranging from 13.1 to 7.1 kWh/m 2 while reducing indoor discomfort by 320 to 131 h for extremely hot climates. Moreover, the sufficiency action related to higher thermostat settings, from 24 to 25 °C to 25–26.5 °C, was the most effective strategy to decrease energy demand. Additionally, there are trade-offs between energy-saving and heat resilience with highly insulated alternatives when ventilation is not adequately addressed. Despite increasing energy savings by 14.4 kWh/m 2, discomfort hours are increased by 256 hours when air conditioning is unavailable, increasing building overheating by 5.1 %.